Effects of warm needle acupuncture on behavioral pain threshold in a rat model of migraine - Liu, Qiang; Qin, Xiaoguang; Luo, Chenglin; Zhao, Zhongting; Xie, Wangjun; Du, Xiaozheng; Qin, Xin (Frontiers in Neurology, 2025)
BackgroundAs a traditional Chinese treatment method, acupuncture has a long history in the treatment of migraine and a rich literature base. As a traditional acupuncture technique, warm needle acupuncture has clearly demonstrated clinical efficacy in the treatment of migraine, although its mechanism of action remains unclear. This study aimed to evaluate the efficacy and safety of warm needle acupuncture in the treatment of migraine in a rat model of migraine by comparing pain threshold and analgesic-related factors among different groups.MethodsThirty Sprague–Dawley rats were randomly divided into control, model, and acupuncture groups, with 10 animals in each group. On day 8, rat migraine models were established by subcutaneous injection of nitroglycerin. The acupuncture group was bilaterally needled once per day at Fengchi, Baihui, Fengfu, and Hegu. Behavioral changes and biochemical alterations among the rats before and after modeling were observed for 7 consecutive days after treatment. The expression of Endothelin-1 (ET-1), interleukin (IL)-6 and tumor necrosis factor-alpha (TNF-α) in the brain stem of the animals were assessed using ELISA. Expression levels of calcitonin gene-related peptide (CGRP) mRNA were determined using real-time quantitative polymerase chain reaction techniques.ResultsAfter treatment, the expression of ET-1, IL-6, TNF-α, and CGRP in the brain stem of the model group was significantly increased compared with that of the control group (p < 0.05), while the expression of IL-6, TNF-α, and CGRP in the brain stem of the acupuncture group was decreased.ConclusionWarm needle acupuncture reduced ET-1 protein levels and promoted the expression of neurotransmitters, such as 5-hydroxytryptamine, in migraine rat model animals. In addition, needle warming acupuncture decreased IL-6, TNF-α, and CGRP levels in the brain stem of the migraine group, which may explain its mechanism of action in treating migraine.